The Use of Molasses as Additive with Different Ensiling Time and Physical Quality, pH and Nutritive of Value Maize Stover Silage - Hartutik Hartutik; Marjuki Marjuki; Asri Nurul Huda; Hazanah Poespitasari Ndaru; Yuanita Nur Arsianty; Binti Nur Rohmah (Jurnal Nutrisi Ternak Tropis, 2021)
The objectives of this experimental research was to determine the effect of different ensiling time of maize stover silage with molasses as additive on physical quality, pH and nutritive value. The experiment used Factorial Randomized Completely Design (RCD) of two factors (maize stover = A and maize stover + 10% molasses = B), 3 ensiling time (0, 7, 14 days) and 4 replications. The treatments consisted of (A0 = maize stover without incubation, A1 = maize stover incubated for 7 days, A2 = maize stover incubated for 14 days) and (B0 = maize stover + 10% molasses without incubation, B1 = maize stover + 10 % molasses incubated for 7 days, and B2 = maize stover + 10 % molasses incubated for 14 days). The variable was measured physical quality, pH and nutritive value. The results showed that incubation time of A and B gave significant effect on physical quality and pH silage, maize stover silage without and with 10 % molasses incubated 14 days gave the best result of physical quality and pH (A = 4.00 and B = 3.89) silage. The result showed that incubation time of A and B gave highly significant effect (P<0.01) on Dry Matter (DM) and Ether Extract (EE), however it did not give significant effect (P>0.05) on Organic Matter (OM). It can be concluded that maize stover silage with 10% molasses incubated for 14 days could increase physical quality, decreased pH and maintain nutritive value.